Gender Equality in Higher Education: Access, Participation, and Academic Leadership - Suardi, Suardi; Yumriani, Yumriani; Ramlan, Herdianty; Mutiara, Indah Ainun; Firdaus, Firdaus; Nur, Rahmat; Nur, Hasruddin; Nur, Syahban; Marsuki, Nur Riswandy; Muchtar, Fitri Yanty; Syarifuddin, Syarifuddin (Journal of Educational Sciences, 2025)
Gender equality in higher education is increasingly recognized as a strategic component of sustainable development, encompassing dimensions of access, participation, and academic leadership. This article examines the challenges, opportunities, and strategies for advancing gender equality in universities. Drawing on more than 50 scholarly articles and policy reports from the past decade, retrieved from Scopus, Web of Science, and Google Scholar, the literature spans both Global North and South contexts, with diverse methodologies quantitative, qualitative, and mixed-method. The systematic selection process applied inclusion criteria such as peer-reviewed status and topical relevance. A narrative synthesis approach was used to extract key themes, including access, participation, structural barriers, and policy measures. While women’s access to higher education has improved, significant disparities persist, especially in STEM disciplines and academic leadership. Barriers such as gender bias, unequal domestic responsibilities, and limited institutional support remain pervasive. Various interventions including gender training, mentoring, and policy reforms have shown mixed effectiveness across contexts. The findings underscore the importance of multidimensional strategies involving stakeholders, embedding gender equity into institutional culture, and enhancing policy monitoring systems. This review provides evidence-based insights and practical recommendations to foster more inclusive and equitable higher education environments globally.